Optimizing STEM Learning in SDN Bringinan with Interactive PhET Technology - Rizal Arifin; Sudarno Sudarno; Yoyok Winardi; Desriyanti Desriyanti; Vijay Adi Mustiko; Norhasnidawani Johari; Ali Selamat (International Journal Of Community Service, 2024)
This program aimed to enhance STEM education at SDN Bringinan, Jambon, Ponorogo, by integrating PhET Interactive Simulations. The program focused on two main topics: energy transfer and energy transformations. Students from grades 4, 5, and 6 were divided into groups and guided by facilitators to explore these concepts using PhET. The program began with problem identification through discussions with the school's Principal and teachers, followed by careful planning and execution over two sessions in August 2024. The first session introduced students to heat transfer, while the second focused on energy transformations. Post-session evaluations showed that students successfully understood and applied these concepts, identifying energy sources, converters, and users, and explaining the process of energy transformations. The success of the program suggests the effectiveness of interactive technology like PhET in improving students' comprehension of complex scientific concepts, highlighting a valuable approach for future educational initiatives.